2017
DOI: 10.3892/ol.2017.5616
|View full text |Cite
|
Sign up to set email alerts
|

Low serum testosterone is associated with tumor aggressiveness and poor prognosis in prostate cancer

Abstract: Abstract. Serum testosterone is a potential marker to distinguish between indolent and aggressive prostate cancer (PCa). The present study aimed to investigate whether low levels of total serum testosterone at diagnosis were associated with aggressive PCa and poor clinical outcomes. In total, 762 non-Hispanic Caucasian men with previously untreated PCa were recruited from The University of Texas MD Anderson Cancer Center (Houston, TX, USA). Patients were categorized into three groups based on their total serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
5
20
0
Order By: Relevance
“…In support of this finding is the observed strong negative correlation between PSA and TT among the patients with hypogonadism and highrisk PSA levels. These findings and observations in this study regarding the relationship between PSA and TT are in accord with the findings in similar studies by Alsharef et al, Garcia-Cruz et al, Schatzl et al, and Tu et al 6,9,10,16 Alsharef et al had investigated the association between serum TT and adverse prognostic features in men with prostate cancer and observed that low serum TT was associated with higher PSA, higher grade, locally advanced and metastatic prostate cancer. However, Alsharef et al had used the serum free testosterone in their study in contrast to the total serum TT employed in this study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In support of this finding is the observed strong negative correlation between PSA and TT among the patients with hypogonadism and highrisk PSA levels. These findings and observations in this study regarding the relationship between PSA and TT are in accord with the findings in similar studies by Alsharef et al, Garcia-Cruz et al, Schatzl et al, and Tu et al 6,9,10,16 Alsharef et al had investigated the association between serum TT and adverse prognostic features in men with prostate cancer and observed that low serum TT was associated with higher PSA, higher grade, locally advanced and metastatic prostate cancer. However, Alsharef et al had used the serum free testosterone in their study in contrast to the total serum TT employed in this study.…”
Section: Discussionsupporting
confidence: 93%
“…However, Tu et al posit that the low TT milieu in men might activate some oncogenic pathways that select for specific molecular features that are indicative of adverse or poor prognostic outcome. 16 While Loeb et al posit that the high or normal TT levels keep the prostate cells and early prostate cancer cells in a differentiated state and that the loss of this TT function secondary to low serum TT may lead to the development of less-differentiated cancer with adverse and poor prognostic features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This stratification is supported by prior studies demonstrating that low testosterone at the time of PC diagnosis is associated with a poorer prognosis after radical prostatectomy or RT and ADT and shorter responses to salvage ADT. [15][16][17][18] If a high PSA response rate (such as a decline in pretreatment PSA of >80% or more stringently achieving an undetectable PSA <0.1 ng/mL) in at least two-thirds of the study cohort is observed, this would provide the basis to support a phase 3 trial in this setting investigating standard ADT with 1 novel agents and their impact on survival. Several points require further discussion.…”
Section: Discussionmentioning
confidence: 99%